Modulated synthesis and isoreticular expansion of Th-MOFs with record high pore volume and surface area for iodine adsorption - Li, Zi-Jian; Ju, Yu; Yu, Bowen; Wu, Xiaoling; Lu, Huangjie; Li, Yongxin; Zhou, Jing; Guo, Xiaofeng; Zhang, Zhi-Hui; Lin, Jian; Wang, Jian-Qiang; Wang, Shuao (Chemical communications (Cambridge, England), 2020)
Modulated synthesis and isoreticular expansion of Th-MOFs enable the stepwise construction of hierarchical complexes in which porosity and functionality can be fine-tuned, affording new Th-MOFs with a record high void space (74.0%), the largest surface area (3396.5 m 2 g −1 ) among thorium materials, and excellent adsorption capacities toward radioactive iodine. Isoreticular expansion of Th-MOFs via modulated synthesis yielded seven hierarchical complexes with superior quality single crystals, record high void space and BET surface area among Th materials, and exceptional iodine adsorption capacities.